2018
DOI: 10.1051/bioconf/20181100036
|View full text |Cite
|
Sign up to set email alerts
|

Species composition dynamics in successive plant assemblages on the northern slopes of the coal mining spoils in the arid areas of Khakassia

Abstract: The results of the study of the species composition dynamics in successive plant communities developing on the northern slopes of the coal mining spoils dating back to the 70s, 80s, 90s and 2000s years in the arid areas of Khakassia, are presented for the first time. During the first 10-15 years of revegetation there was an increase in taxonomic diversity in the successive plant assemblages. Endemic species of the Fabaceae family, common for the bunch grasses steppes and stony steppes of Khakassia, were not fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…Issue) : 2022 native. A research by Malakar and Joshi (2020) on the Ranigunj coalfield found 10 tree species in a natural forest close to the coalfield and 30 tree species in various overburden dumps while Safronova et al (2018) recorded 40 species belonging to 35 genera and 18 families. Dalbergia sissoo (46.28) was found the most dominant and important tree species in all the communities which only accounts for 15.43 % of the area (Table 1) which showed resistance to the adverse climatic condition of mining areas resulting in sustainable reclamation of area (Juwarkar and Singh, 2007) while the lowest IVI value (1.15) wasfor Mitragyna parviflora.…”
Section: Tree Species Composition and Diversity Indexmentioning
confidence: 99%
“…Issue) : 2022 native. A research by Malakar and Joshi (2020) on the Ranigunj coalfield found 10 tree species in a natural forest close to the coalfield and 30 tree species in various overburden dumps while Safronova et al (2018) recorded 40 species belonging to 35 genera and 18 families. Dalbergia sissoo (46.28) was found the most dominant and important tree species in all the communities which only accounts for 15.43 % of the area (Table 1) which showed resistance to the adverse climatic condition of mining areas resulting in sustainable reclamation of area (Juwarkar and Singh, 2007) while the lowest IVI value (1.15) wasfor Mitragyna parviflora.…”
Section: Tree Species Composition and Diversity Indexmentioning
confidence: 99%
“…Accordingly, the restoration of aquatic plants is deemed essential for effective wetland ecological management [11]. The hydrological processes involved significantly contribute to the formation and evolution of wetland ecosystems, thereby impacting the growth and progression of wetland vegetation [12,13]. Water level fluctuations serve as a key indicator in this process [14,15].…”
Section: Introductionmentioning
confidence: 99%